Strategi Humas Perguruan Tinggi dalam Membangun Reputasi: Studi Alih Status IAIN Bengkulu menjadi UIN Fatmawati Sukarno Bengkulu - Rohmad Fadli; Gushevinalti Gushevinalti; Mas Agus Firmansyah (JURNAL ILMIAH SYI'AR, 2021)
This study aims to determine the public relations branding strategy in the case of the transfer of status from the Bengkulu State Islamic Institute (IAIN Bengkulu) to the State Islamic University of Fatmawati Sukarno Bengkulu (UIN Bengkulu). We use qualitative data that produces data in the form of written or spoken words from people and observed behaviour. The selection of informants in this study used purposive sampling, which is to determine information with certain considerations that can provide maximum data. The results of the study stated that the public relations strategy in an effort to brand higher education followed the vision, mission and goals of the university, including the transfer of status from IAIN Bengkulu to UIN Bengkulu. The branding strategy that has been carried out is the use of appropriate technology. Public relations publicity is a strategy carried out by the public relations, publication and documentation subdivision of IAIN Bengkulu in building a reputation. The strategy in building reputation is carried out by presenting information on activities and advantages through the official media of IAIN Bengkulu and media that disseminate with IAIN Bengkulu in spreading the news to the public.